Expression of Helper and Regulatory T Cells in Atopic Dermatitis: A Meta-Analysis - Zhang, Dao-jun; Hao, Fei; Qian, Tian; Cheng, Hai-xing (Frontiers in Pediatrics, 2022)
Background Atopic dermatitis (AD) is a common inflammatory skin disease, with the incidence peaks in infancy. A meta-analysis was performed to assess the levels of T helper type 22 (Th22) cells, T helper type 17 (Th17) cells, interleukin (IL)-17, and Tregs in peripheral blood of patients with AD. Methods A comprehensive literature search was performed in PubMed, Embase, China National Knowledge Internet, and Wan-fang Data from the day of inception of this study to July 2021. Two authors independently extracted the data, which were pooled and calculated using Stata software version 15. Results A total of eight studies met the inclusion criteria. Compared with control group, patients with AD had an increased proportion of Th22 cells [weighted mean difference (WMD) = 2.07, 95% CI (1.33, 2.81), p < 0.001], Th17 cells [WMD = 1.04, 95% CI [0.66, 1.43], p < 0.001], IL-17 [WMD = 17.56, 95% CI (11.1, 24.03), p < 0.001], and a decreased proportion of Tregs [WMD = −2.49, 95% CI (−2.93, −2.05), p < 0.001] in peripheral blood. The subgroup analysis showed that patients with higher disease severity had higher levels of Th22 [mild: WMD = 1.33, 95% CI (1.24, 1.41), p < 0.001; moderate: WMD = 1.41, 95% CI (1.36, 1.54), p < 0.001; severe: WMD = 3.46, 95% CI (3.34, 2.81), p < 0.001] and lower levels of Tregs [mild: WMD = −1.43, 95% CI (−1.75, −1.11), p < 0.001; moderate: WMD = −2.16, 95% CI (−2.46, −1.86), p < 0.001; severe: WMD = −2.96, 95% CI (−3.25, −2.67), p < 0.001] in peripheral blood compared to healthy controls. Conclusion The random effect model of the meta-analysis showed patients with AD had an increased proportion of Th22 cells, Th17 cells, and IL-17, whereas a decreased proportion of Tregs was found in peripheral blood. The results demonstrated that Th22 cells, Th17 cells, IL-17, and Tregs may be involved in the pathogenic mechanisms of AD.